Development of Educational Media based Film Animation Podtoon on National Income Material - Putri Sari M.J. Silaban; Aurora Elise Putriku; Novita Indah Hasibuan (Formosa Journal of Science and Technology, 2023)
This research uses research and development (R&D) methods using the ADDIE model. For the small test sample, 10 college students were randomly selected. Porton Movie. tests on college students. Data analysis techniques used are quantitative and qualitative data analysis techniques. The results of research and development are educational materials based on Poodton cartoons that can be accessed from smartphones through YouTube and Google Drive applications which can also be downloaded offline.  In the practical test, students also gave a positive response with an average overall score of 5.80 included in the very practical category as well as an effectiveness test using the t-test table for significance levels α = 5% = 0.05 and df = 9, then obtained t at t hit = 17.72 and t tab = 1.833 with the conclusion The value of t hit > t tab, so it is said that there is effectiveness (significance) The development of introductory teaching materials for macroeconomics based on poodton animated films with a significance level of 5% is very effective.